The Influence of the South China Sea Conflict on the Security and Defence of the Indonesian State - Muhammad, Hatta Abdi; Beriansyah, Alva; Baidawi, Ahmad (International Journal of Contemporary Sciences (IJCS), 2024)
This research examines the influence of the South China Sea (SCS) conflict on Indonesia's resilience and security. Indonesia began to be drawn into the SCS conflict in 2010, after China claimed Indonesia's EEZ in the northern region, specifically the Natuna Islands. China's unilateral claims continued and peaked in 2016 when Chinese fishing vessels carried out illegal fishing activities in Natuna waters. Until now, Chinese ships still often enter Indonesia's borders. China's assertive behavior is considered an action that violates Indonesia's national sovereignty, therefore Indonesia is trying to maintain and secure its sovereignty and national interests in the Natuna Islands even though it is not part of the countries in dispute. By using qualitative research methods that combine the strengths of primary and secondary data, the findings show that if left unchecked, SCS conflicts could threaten Indonesia's resilience, security and sovereignty. Under Joko Widodo's government, Indonesia responded to the SCS conflict through diplomatic efforts and military alertness.